The Civil-Military Relations for State Defense Awareness - Selfira Salsabilla; Hikmat Zakky Almubaroq (Department of Political Science - Universitas Sains Al-Qur’an, 2022)
TNI Manunggal Membangun Desa (TMMD) is one form of military operations other than war as regulated in Law Number 34 of 2004 concerning the ability of the Indonesian National Army (TNI) to assist local government tasks in development. It is a collaborative activity between the regional commando unit at the district level (Kodim), where the implementation process fulfils the basic elements in management. The formulation of the problem in this research is how the basic management process in the implementation of TMMD Sengkuyung Phase 3 Kodim 0707/Wonosobo and how the development of state defense awareness can be carried out through these activities. The purpose of this research is to explain how the basic management process in the implementation of TMMD Sengkuyung Phase III Kodim 0707/Wonosobo and find out what activities are carried out through TMMD Sengkuyung Phase III for the Year 2021 Kodim 0707/Wonosobo in order to increase awareness of defending the state. The method used in this study is a qualitative research method where the basic theory of management testing will be carried out on the phenomenon that occurs, namely the process of implementing TMMD Sengkuyung as an effort to increase awareness of defending the country.